KEEFEKTIFAN MEDIA CANVA UNTUK MENINGKATKAN HASIL BELAJAR BAHASA INDONESIA KELAS V SD - Tri Setyani, Erinda; Wijayanti, Arfilia; Pariyati, Pariyati (Universitas Negeri Medan, 2024)
Abstract: Cognitive learning outcomes in Indonesian language subjects for class V students at SDN Pandeanlamper 01 Semarang tend to be low because teachers use conventional learning and have not utilized technology in learning. The aim of this research was to determine the cognitive learning outcomes of Indonesian language subjects for class V students at SDN Pandeanlamper 01 Semarang using Canva media whether they could meet the KKM or not. This research is quantitative research with an experimental type. The data analysis techniques used are descriptive statistical analysis and hypothesis testing using the normality test, ngain score test and t test. The results of this research show that Canva media causes the Indonesian language learning outcomes of class V students at SDN Pandeanlamper 01 to be better. This is clearly visible between the mean pre-test score of 68 and the mean post-test score of 83. The test score was 0,3≤0,4933≤0,7 which means the level of effectiveness is moderate. Meanwhile, the mean percent value obtained was 49.3301. Based on the interpretation of effectiveness, a value of 40-55 means quite effective or can mean that the use of a method or treatment is quite effective. The t-test shows that the value of tcount = 12.514 is higher than the value of ttable = 2,042, which means that the data shows a significant difference between the effectiveness of learning media before and after using Canva media. Keyword: Canva Media, Learning Outcomes Abstrak: Hasil belajar kognitif mata pelajaran Bahasa Indonesia siswa kelas V SDN Pandeanlamper 01 Semarang cenderung rendah karena guru menggunakan pembelajaran yang konvensional dan belum memanfaatkan teknologi dalam pembelajaran. Tujuan dilakukan penelitian ini adalah untuk mengetahui hasil belajar kognitif mata pelajaran Bahasa Indonesia siswa kelas V SDN Pandeanlamper 01 Semarang dengan menggunakan media canva bisa memenuhi KKM atau tidak. Penelitian ini adalah penelitian kuantitatif dengan jenis eksperimen. Teknik analisis data yang digunakan yaitu statistik deskriptif dan pengujian hipotesis menggunakan uji normalitas, uji ngain skor serta uji t. Hasil penelitian ini menunjukkan media canva menyebabkan hasil belajar bahasa indonesia siswa kelas V SDN Pandeanlamper 01 menjadi lebih baik. Hal ini terlihat jelas antara nilai mean pre-test sebesar 68 dengan nilai mean post-test sebesar 83. Uji ngain skor sebesar 0,3≤0,4933≤0,7 yang artinya tingkat efektivitasnya sedang. Sedangkan ngian persen nilai mean yang diperoleh sebesar 49,3301. Berdasarkan tafsiran efektifitas bahwa nilai 40-55 yang artinya cukup efektif atau bisa diartikan penggunaan suatu metode atau pengobatan cukup efektif. Uji-t menunjukkan nilai thitung = 12,514 lebih tinggi dari pada nilai ttabel = 2,042 bisa diartikan bahwa data tersebut ada perbedaan yang signifikan antara keefektifan media pembelajaran sebelum dan sesudah menggunakan media canva.Kata Kunci: Media Canva, Hasil Belajar